A Narrative Evaluation of a Grief Support Camp for Families Affected by a Parent's Suicide - Silvén Hagström, Anneli (Frontiers in Psychiatry, 2021)
Background: Children of parents who suffer mental ill-health and die by suicide are vulnerable to developing psychological and social problems themselves; they also have a severely elevated risk of dying at a young age – particularly through suicide. This highlights the need to design supportive measures that can counteract such negative developments after a parent’s suicide. Aim: This narrative evaluation of a grief support camp for families affected by a parent’s suicide arranged by the non-profit organization Children’s Rights in Society in Sweden investigates whether children [N=11] and parents [N=11] perceived their participation as meaningful and, if so, in what way, and the changes to which the program was said to have contributed. Methods: Family members were invited to reflect on their experiences in narratively structured interviews that took place 18 months after participation. Their narrated experiences were analyzed to examine how the program was integrated into their biographies and with what significance. “Narratives of change” (Baú, 2016) were identified in particular in order to grasp the self-perceived effects of participation. Results: Both children and parents attributed major significance to their encounters with other suicide bereaved. This led to support exchange and normalization, which countered a perceived “suicide stigma” in everyday life. Help to narratively construct destigmatizing understandings of suicide was also said to have relieved self-blame and shame. Overall, the participants described changes in the form of a better-informed position in grief, increased manageability and enhanced family communication. The parents also reported improved ability to support their children and a more hopeful view of life ahead. Conclusion: The evaluation showcases how this psychoeducational intervention, at a relatively low cost compared to traditional approaches, has great potential to lessen the negative effects of a suicide in the family by assisting families with psychological processing and de-stigmatization. Parental resources are also strengthened, which can serve as continuing support for the children.